Effects of Sport-Based Interventions on Executive Function in Older Adults: A Systematic Review and Meta-Analysis Protocol - Contreras-Osorio, Falonn; Ramirez-Campillo, Rodrigo; Cerda-Vega, Enrique; Campos-Jara, Rodrigo; Martínez-Salazar, Cristian; Arellano-Roco, Cristián; Campos-Jara, Christian (Brain sciences, 2022)
Background: Moderate-to-vigorous intensity exercise programs have proven to exert positive effects on the cognitive performance of older people. However, the specific effects sport-based exercise programs have on cognitive performance, upon executive functions, remain unclear. Therefore, the purpose of this study is to clarify the effects of sport-based exercise programs on executive functions in older adults, through a systematic review protocol of the scientific literature, with a meta-analysis. Methods: The search was performed in the Web of Science, PubMed, Scopus, and EBSCO electronic databases by combining keywords and different medical subject headings (MeSH) to identify and evaluate the relevant studies from inception up until June 2022. This study considers longitudinal studies with at least one experimental group and pre- and post-intervention measurements involving healthy older adults of 60 years of age or older. Studies have to consider one or more measures of executive function, including dimensions of working memory, inhibition, and cognitive flexibility, in order to meet the eligibility criteria for inclusion in this report. The Physiotherapy Evidence Database (PEDro) scale was used for methodological quality assessment studies. The DerSimonian and Laird random-effects model was used to compute the meta-analyses and report effect sizes (ES, i.e., Hedges’ g) with 95% confidence intervals (95% CIs), and a statistical significance set at p ≤ 0.05. The ES values were calculated for executive function globally and for each dimension of executive function (e.g., working memory, inhibition, cognitive flexibility) in the experimental and control/comparator groups using the mean and standard deviation values before and after the intervention period. Conclusions: Our systematic review aims to clarify the effects of sport-based exercise programs on executive functions in older adults. The results may help practitioners and stakeholders to provide better evidence-based decisions regarding sport-based exercise program implementation for older adults, and to help them to optimize cognitive functions during the aging process. Ethical permission is not required for this study. Systematic review registration: this systematic review is registered with the International Prospective Register of Systematic Reviews (PROSPERO; registration number: CRD42022284788).